2014
DOI: 10.1007/s12032-014-0925-4
|View full text |Cite
|
Sign up to set email alerts
|

Percent free prostate-specific antigen does not improve the effectiveness of prostate cancer detection in Chinese men with a prostate-specific antigen of 2.5–20.0 ng/ml: a multicenter study

Abstract: The prostate-specific antigen (PSA) "gray zone" in Chinese men is likely higher than the traditional value (2.5-10.0 ng/ml) since the incidence of prostate cancer in Chinese men is relative low. The utility of percent free PSA in predicting prostate cancer is based on Western populations and may introduce sizable bias when applied to a Chinese cohort. We assessed the efficacy of percent free PSA in predicting prostate cancer in Chinese men with a PSA of 2.5-10.0 and 10.1-20.0 ng/ml. A total of 558 men with a P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
2
11
0
1
Order By: Relevance
“…Consistent with this finding, Catalona et al [3] reported median tPSA values of 5.6 ng/mL and 5.9 ng/mL in their benign and cancer groups, respectively; these values were not significantly different. Similar findings were reported in a study of Chinese men with tPSA levels of 2.5–20 ng/mL [16]. The men were divided into two groups based on their tPSA value: 2.5–10 ng/mL and 10.1–20 ng/mL.…”
Section: Discussionsupporting
confidence: 79%
“…Consistent with this finding, Catalona et al [3] reported median tPSA values of 5.6 ng/mL and 5.9 ng/mL in their benign and cancer groups, respectively; these values were not significantly different. Similar findings were reported in a study of Chinese men with tPSA levels of 2.5–20 ng/mL [16]. The men were divided into two groups based on their tPSA value: 2.5–10 ng/mL and 10.1–20 ng/mL.…”
Section: Discussionsupporting
confidence: 79%
“…Although studies indicated a similar effectiveness of %fPSA in Chinese and other East Asian populations compared with the Western population, 15 16 recent reports illustrated a limited improvement of %fPSA in younger Koreans with a PSA of 4.0–10.0 ng ml −1 and in Chinese men with PSA 2.5–10 ng ml −1 and 10.1–20.0 ng ml −1 . 11 17 In our data set, the AUC of %fPSA was also close to that of PSA in the whole cohort but significantly higher than PSA in the older subgroup. However, there were only 274 patients with a PSA of 2.5–10.0 ng ml −1 and 284 patients with a PSA of 10.1–20.0 ng ml −1 in that study.…”
Section: Discussionsupporting
confidence: 67%
“…The diagnostic efficacy of %fPSA is weaker in Chinese and Korean populations than Western populations [ 11 , 12 ]. Some studies excluded %fPSA from multivariable nomograms for PCa prediction in the Chinese population [ 13 ].…”
Section: Introductionmentioning
confidence: 99%